2016
DOI: 10.1016/j.dt.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic behavior of boron carbide reinforced AA7075 aluminium alloy using friction stir processing – An experimental study and analytical approach

Abstract: High strength-to-weight ratio of non-ferrous alloys, such as aluminium, magnesium and titanium alloys, are considered to be possible replacement of widely accepted steels in transportation and automobile sectors. Among these alloys, magnesium is self explosive and titanium is costlier, and aluminium is most likely to replace steels. Application of aluminium or its alloys is also thought of as an appropriate replacement in defence field, especially to enhance the easiness in mobility of combat vehicles while ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…The hybrid composites consist of more than one reinforcement particles. The Al/B 4 C/TiC hybrid composites [78] exhibited higher tensile strength as compared to TiC fabricated composite as shown in Fig. 12.…”
Section: Reinforcements and Composite Propertiesmentioning
confidence: 92%
“…The hybrid composites consist of more than one reinforcement particles. The Al/B 4 C/TiC hybrid composites [78] exhibited higher tensile strength as compared to TiC fabricated composite as shown in Fig. 12.…”
Section: Reinforcements and Composite Propertiesmentioning
confidence: 92%
“…When aluminum alloys are subjected to FSW/FSP, being a material with high stacking fault energy (γ SFE ≈ 160-200) [88], generally CDRX acts as main grain refining mechanism. Fine grains with more HAGBs are formed in the fabricated composites as a result of CDRX [35,43,45,51,61,89,90]. At the time of deformation of metal at elevated temperature, two opposite phenomena take place simultaneously, i.e., formation of dislocation and dynamic recovery, which determines the dislocation density in the material.…”
Section: Microstructural Characterization Of Amcs Fabricated By Fspmentioning
confidence: 99%
“…Sudhakar et al [90] prepared AA7075 matrix composite by adding different sizes of B 4 C particles and observed that penetration of projectile during ballistic impact test reduced with reduction in particle size. The hard particles acted as barrier to the projectile movement, and consequently, the projectile tip was damaged due to abrasive nature of the particles.…”
Section: Other Mechanical Propertiesmentioning
confidence: 99%
“…It is, therefore, certain that in the future, steel might go into extinction wherein high strength and low-density materials such as aluminium, titanium, and magnesium might replace the steel. On this awareness and since titanium is very costly and magnesium is self-explosive, therefore aluminium might be the one that will likely replace steel in some of the prominent industries where steel functions today such as transportation, aerospace, automobiles, and defense sectors (Ikumapayi et al, 2019b;Sudhakar et al, 2016). The utilization of any of these engineering materials effectively and efficiently is very paramount for the manufacturing and designing of various structures, machines as well as vehicles, etc.…”
Section: Introductionmentioning
confidence: 99%